2020
DOI: 10.35314/inovish.v5i2.1450
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Using Whatsapp to Enhance Students’ Learning of Advanced Listening Class

Abstract: Education system has developed rapidly, technology has invaded our life, everyone has smart phone these days, using WhatsApp, Facebook, Twitter, Instagram, Telegram, etc. No one can deny that the generation we teach these days, has become addicted to these applications, for social relationship and fun. This study was conducted in English Departmen especially Advanced Listening class. The population of the study were 32 female and 4 male students from 4st level who were studying English Program. The researcher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Thus, this study strengthens several previous similar studies, such as (Yuniarti, 2020); Indiran et al, 2022). Their study revealed that the use of WhatsApp as a mobile phone and web-based application can be used to chat (text and sound), collaboration for knowledge sharing and educational interaction between teachers and students as well as between students.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, this study strengthens several previous similar studies, such as (Yuniarti, 2020); Indiran et al, 2022). Their study revealed that the use of WhatsApp as a mobile phone and web-based application can be used to chat (text and sound), collaboration for knowledge sharing and educational interaction between teachers and students as well as between students.…”
Section: Discussionsupporting
confidence: 88%
“…Yuniarti [54] conducted an examination utilizing WhatsApp to improve students' acquisition of advanced listening abilities in English language lessons by analyzing their opinions and tracking their development after using the program to facilitate learning English. The study sample included 32 female and four male pupils.…”
Section: Whatsapp and Listening Skillsmentioning
confidence: 99%